Fiscal Decentralization and Regional Economic Growth: Empirical Evidence from Indonesian Districts - Ahmad Fauzi Rahman; Rachmad Kresna Sakti; Michael J. Thompson (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Fiscal decentralization has become a central policy instrument in Indonesia’s regional development strategy since the early 2000s. However, empirical findings on its impact on regional economic growth remain inconclusive. This study examines the effect of fiscal decentralization on economic growth across Indonesian districts by synthesizing evidence from panel data–based empirical studies and contextualizing them within decentralization theory. The study adopts a qualitative systematic review and comparative empirical synthesis approach, focusing on indicators such as regional own-source revenue, intergovernmental transfers, and government expenditure. The findings indicate that fiscal decentralization generally exerts a positive influence on regional economic growth, particularly through increased local revenue capacity and productive government spending. However, the impact varies across regions due to differences in fiscal capacity, governance quality, and dependency on central government transfers. Several studies also reveal that excessive reliance on general allocation funds may weaken growth incentives. This study contributes to the literature by integrating diverse empirical results into a coherent analytical framework and highlighting policy conditions under which fiscal decentralization promotes sustainable regional growth. The findings support the need for strengthening local fiscal autonomy while improving accountability and expenditure efficiency at the district level.